Efeito do peróxido de carbamida e dos metais presentes no amálgama dental sobre a atividade da δ-ala-d hepática (e. C.: 4.2.1.24), e os níveis de peroxidação lipídica em ratos - Neisse, Fernanda (2006)
Tooth bleaching is an aesthetic procedure that is usually carried out with products containing carbamide peroxide, which has a potential deleterious effect mediated by hydrogen peroxide formation. Dental amalgam has still been widely used for posterior teeth restorations, despite its mercury content. There is concern that hydrogen peroxide generated from bleaching agents can cause enhanced metal ion release from dental amalgam restorations when in contact, but there are few studies about the synergistic systemic toxic effects of these products. The aim of the present study was to investigate the possible toxic effects of carbamide peroxide in vivo after oral administration, and in vitro, as dental amalgam metals toxicity. The parameters studied for characterization of toxicity were hepatic δ-aminolevulinate dehydratase (δ - ALA-D) activity, 2-thiobarbituric acid reactive substance (TBARS) levels in liver, brain, kidney and dental pulp of rats, and in addition the topic effect over palatal mucosa, which was investigated by histological study. In vivo, exposure to carbamide peroxide did not change TBARS levels in liver and dental pulps, or liver δ - ALA-D activity. However, only the 35% carbamide peroxide treatment provoked an increase in the epithelium thickness, which was associated with an elevation in the number of epithelium cell layers, and an elevation in epithelium basal cell layer dimension. Carbamide peroxide produced a significant increase in TBARS production in vitro when tested at extremely high concentrations in liver, brain and dental pulp. CuSO4 and SnCl2 produced a significant decrease in liver TBARS levels when tested at concentrations of 100 and 200 μM. Otherwise in brain, 100 μM CuSO4 caused an increase in TBARS production. In dental pulp, 100 and 200 μM HgCl2 caused an increase in TBARS levels production. When amalgam metals constituents and carbamide peroxide dissolved in carbopol were incubated together, carbopol and 200 μM SnCl2 significantly decreased brain TBARS production. Carbopol, the gel vehicle, caused a decreased TBARS production in all tissues. In conclusion, carbamide peroxide, CuSO4 and HgCl2 were found to have some pro-oxidant activity over tissues. Therefore, care is needed when bleaching treatment is performed in amalgam restored teeth, because pulp tissue may be overwhelmed by the concomitant toxic activity of these substances.